2013
DOI: 10.3727/096368912x657882
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β Delivery via Human Neural Stem Cell Abates Glial Scar Formation in Spinal Cord Injury

Abstract: Glial scar formation is the major impedance to axonal regrowth after spinal cord injury (SCI), and scar-modulating treatments have become a leading therapeutic goal for SCI treatment. In this study, human neural stem cells (NSCs) encoding interferon-β (INF-β) gene were administered intravenously to mice 1 week after SCI. Animals receiving NSCs encoding IFN-β exhibited significant neurobehavioral improvement, electrophysiological recovery, suppressed glial scar formation, and preservation of nerve fibers in les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 48 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…It has shown neuroprotective effects that are associated with reduced pro-inflammatory cytokine expression and increased anti-inflammatory cytokine expression in sites of injury. Recently, it was reported that IFN-b gene delivery suppresses astrocyte activation and glial scar formation after spinal cord injury [45,46]. In contrast to IFN-b, IL-6 is thought to contribute to astrogliosis in response to brain injuries [34,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has shown neuroprotective effects that are associated with reduced pro-inflammatory cytokine expression and increased anti-inflammatory cytokine expression in sites of injury. Recently, it was reported that IFN-b gene delivery suppresses astrocyte activation and glial scar formation after spinal cord injury [45,46]. In contrast to IFN-b, IL-6 is thought to contribute to astrogliosis in response to brain injuries [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…TLR3 activation can modulate the TLR4/NF-kB signaling pathway and thus may inhibit generation of proinflammatory cytokines such as TNF-a and IL-6 [6,13,19,48]. Studies in experimental spinal cord injury models showed that TLR4 expression is increased in the gliosis lesion site and that TLR4 mutant mice exhibit sustained locomotor deficits and increased demyelination, astrogliosis, and macrophage activation [45,49]. In addition, it was suggested that TLR4 signaling in the spinal cord is required for exogenous IFN-b to suppress glial scar formation [45,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo treatment with peptide amphiphile could reduce glial scar formation, increase the number of oligodendroglia at the site of spinal cord injury and resulted in significant behavioral improvements (Tysseling-Mattiace et al, 2008). IFN-β-encoding could help transplanted NSCs to inhibit glial scar formation in spinal cord injury through the stimulation of TLR4 signaling (Nishimura et al, 2013). However, as we described before, glial scar can offer wound healing, limits the inflammation and protects the healthy tissue.…”
Section: Microglia Is a Double Edged Sword: Either Exacerbating Degenmentioning
confidence: 79%
“…This was accomplished using a liposome-mediated interferon (IFN)-b gene delivery method, or by IFN-b delivery with intravenous injection of genetically engineered neural stem cells. 38,39 Inhibition of glial scar formation is a potential strategy for treating SCI. Whether reactive astrocytes are beneficial is still controversial.…”
Section: Figmentioning
confidence: 99%